EMISSION MEASUREMENT AND OPTIMIZATION OF COMBUSTION PROCESS IN THE BOILERS - KONIAR, Jan (Trends in education, 2010)
The present contribution is focused to the emission measurement and optimization of combustion process in experimental boiler that can be utilized as a didactic tool in educational process. The model of the boiler can to be also applied in the study of combustion flow in a heat exchanger of the boiler.
Keywords: emissions measurement; combustion; boiler.